Crescimento e desempenho fotoquímico do processo fotossintético em abacaxizeiro "Vitória" - Zamperlini, Gabriela Pessotti (2010)
In order to increase knowledge about the pineapple crop, particularly the cultivar 'Vitória', a hybrid resistant to fusariosis, this work evaluated the growth and the photosynthetic activity of plants cultivated at the Experimental Farm of Incaper in Sooretama, State of Espírito Santo. In a completely randomized block design, the plant height and leaf length "D", the contents of photosynthetic pigments and the photochemical efficiency were monitored, from the sucker stage to the end of the reproductive stage. The pineapple cv. Vitória were smaller than those of pineapple cultivars Pérola and Smooth Cayenne, which are the most cropped in Brazil. The content of photosynthetic pigments (chlorophyll a and b and pigments carotenoids) increased during the vegetative stage and remained stable until the last months of analysis, when he suffered a fall. The analysis of fluorescence transient parameters showed a increase in the density of active reaction centers of photosystem II (RC/ABS), in the strength of photochemical reactions (fP0/(1-fP0)), in force related to the reactions after the reduction of QA- (?0/(1-?0)), and performance of the reactions of oxidation-reduction in photosystem I (dR0/(1-dR0)) during the vegetative stage, resulted in increased of vitality index (PIABS) and the total index of vitality (PITOTAL) of plants at the end of vegetative period. These indices showed a reduction in their values three weeks after floral induction, indicating an inhibition of photosynthesis, which shows a sensitivity of plants to induction. However, the pineapples ‘Vitória’ appear to have efficient mechanisms for reduction of damage to the photochemical apparatus, since there was a recovery of RC/ABS, fP0/(1-fP0) and ?0/(1-?0) during the reproductive stage. These results suggest that the rates of photochemical performance (PIABS and PITOTAL) were parameters sensitive to floral induction, proved to be effective in detecting physiological changes occurring during the vegetative and reproductive stage of plants of pineapple 'Vitória'